Book review: Heine, Michael and Hansjörg Herr (2021): The European Central Bank, Newcastle upon Tyne, UK (208 pages, Agenda Publishing, hardcover, ISBN 978-1-78821-294-6; softcover, ISBN 978-1-78821-295-3; ebook, ISBN 978-1-78821-296-0) - Torsten Niechoj (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2021)
In 2020, EJEEP published a special issue on 'The euro at 20 – macroeconomic challenges' with contributions by Bénassy-Quéré (2020), Bibow (2020), Zezza (2020), Bofinger (2020) and Constâncio (2020), who critically reviewed the establishment, evolution and current state of the euro area. The monograph at hand by Michael Heine and Hansjörg Herr offers a rich fundus of institutional, empirical and analytical information in historical perspective that is necessary to understand such debates on monetary policies in the euro area. Moreover, the two authors present their own post-Keynesian view
Keywords: 330